Modern Families: Parenting desire, intention, and experience among portuguese lesbian, gay, and bisexual individuals. - Costa, Pedro Alexandre (2017)
The aim of this study was to examine parenting desire, intention, and experience among a sample of lesbian, gay, and bisexual individuals (N = 568) from Portugal between the ages of 18 and 76 years. Approximately 7% (n = 38) reported having children, with the majority stating a biological kinship with their children primarily from previous heterosexual relationships. The central focus of the current study includes participants without children (n = 530), on average 12 years younger than those with children. Among this group, 65% stated a desire to have children and 56% stated the intention to have children in the future. A multiple regression revealed that young age, involvement in lesbian, gay, bisexual, and transgender events, and low religiosity significantly predicted parenting intention. To further explore the effects of age on parenting intention, an analysis of variance was conducted. Younger participants reported significantly stronger parenting intention, and these differences were detected between each age/developmental group.